Contemporary Civilization Debates, Islamic Modernism and Mehmet Akif in the Turkish Press from the Second Constitutional Era to the Republic - Nuri Sağlam (Yakın Dönem Türkiye Araştırmaları)
After the declaration of the Second Constitutional Monarchy, the great disasters Türkiye experienced one after the other in the face of Christian Europe led to long-term increasingly heated debates in the Turkish press, especially around the concepts of religion and civilization. The focus of all these civilizational debates involved constant comparisons and contrasts between Islam and Christianity and discourses on how to establish a principal consubstantiality between Islam and Protestantism. Therefore, this article outlines the discourses of certain intellectuals, namely Ziya Gökalp and Celal Nuri İleri, who referred only to Protestant European societies as a criterion of contemporary civilization, stating that a Lutheran reform should be made in Islam. The following sections present a few examples of the theological and practical fatwas of certain Islamic scholars who used religion as a political tool or a tool of social pressure for their own personal comfort, justifying all these reformist discourses. Finally, the article mentions the unique place of Mehmet Akif, who undoubtedly holds a distinguished position in the heart of the Muslim Turkish nation with regard to Islamic modernism. In connection to this, the work also mentions how certain discourses of Western liberal intellectuals who distorted some of Akif’s statements about the concept of civilization and declared him to be an “enemy of civilization” lacked any rational basis, not only in terms of semantics but also syntactics.